EQUATIONS SHOWING THE NATIONAL WORLD PICTURE IN THE WORKS OF DULAT ISABEKOV - Jandos Abdazimovich Bayzakov (Western European Studies, 2024)
"Equality is one of the categories in which national peculiarities of artistic thinking are collected, national differences of worldview are collected."
Keywords: comparison; epithet; national world; national psychology